Multiple spindle cell lipomas of the tongue: A case report. Issue 5 (September 2016) - Minakawa, Yasuyuki; Sakamoto, Yosuke; Ishii, Yukiko; Koike, Kazuyuki; Yamatoji, Masanobu; Nakashima, Dai; Higo, Morihiro; Kasamatsu, Atsushi; Shiiba, Masashi; Uzawa, Katsuhiro; Tanzawa, Hideki
Abstract: Spindle cell lipoma (SCL) is a rare benign adipocytic tumor typically arising in the upper neck, back, and shoulders and less commonly in the oral cavity. To our knowledge, only three cases of multiple SCLs of the tongue have been reported previously. We describe a rare case of multiple SCLs of the tongue. A 68-year-old man presented with a 2-year history of a painless swelling measuring 42 and 19 mm in the left side of the tongue. Magnetic resonance imaging showed two well-demarcated lesions that were internally homogeneous. A biopsy was performed for histologic evaluation. With a preoperative diagnosis of multiple lipomas of the tongue, we resected the tumors surgically under general anesthesia. Histopathologic evaluation showed that the lesions were comprised of mature adipocytes with admixed spindle cells in a fibrous myxoid stroma. Immunohistochemically, the lesions included spindle cells that were positive for CD34 and negative for S-100 and CDK4. The final diagnosis of SCL was made based on these findings. The patient was followed for 12 months without a recurrence.